Museum as a tool for developing students’ cognitive competence - Makhanov, N.I.; Baisarina, K.K. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The relevance of the article is due to the close attention of the government of the Republic of Kazakhstan to the issues of preserving and enhancing cultural and historical values, historical self-identification of the peo-ples of Kazakhstan at the present stage of development of the state. Local history and museum practice can provide an opportunity to take an objective look at the history of the development and study of the region, the stages of museum construction, the dynamics of development and modern practice of museums in Kazakh-stan. In this regard, the article examines the pedagogical and methodological potential of students’ historical and educational activities in the study of regional history. The authors of the article highlight the importance of studying regional material in the formation of students’ cognitive competence.
Мұражай ― оқушылардың танымдық құзыреттілігін дамыту құралы ретінде
Музей как инструмент развития познавательной компетентности учащихся
Keywords: history of Kazakhstan; local history; museum; museums of Kazakhstan; cognitive competence of students; museum pedagogy; regional history